Coincidental Onset of Ischemic and Hemorrhagic Stroke in The Brainstem - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2010)
Coincidence of ischemic and hemorrhagic stroke in the acute phase is a rare condition. A patient with uncontrolled hypertension and hypercholesterolemia presented with a sudden onset mild hand paresis that rapidly evolved to hemiparesis over the next few hours. Neuroradiologic investigations revealed a right-sided acute hemipons infarct and a hemorrhage in the anterior territory of infarction. Uncontrolled atherosclerotic risk factors such as hypertension and hyperlipidemia together with antithrombotic therapy seem to be the major reasons for the coincidental presence of both ischemic and hemorrhagic lesions in this patient.
Keywords: Brainstem; pons; hemorrhage; ischemia; antithrombotic; gradient echo; PONTINE HEMORRHAGE; CIRCULATION; INFARCTS